Human milk oligosaccharides and its acid hydrolysate LNT2 show immunomodulatory effects via TLRs in a dose and structure-dependent way. (August 2019) - Cheng, Lianghui; Kiewiet, Mensiena B.G.; Groeneveld, Andre; Nauta, Arjen; de Vos, Paul
Graphical abstract: Highlights: HMOs show immunomodulatory effects via TLRs. HMOs show different activation and inhibition effects on TLR signaling pathways. The effects of HMOs on TLR signaling and immunomodulation of macrophages are dose and HMO-structure dependent. Acidic hydrolysis of HMOs enhance HMO's immune modulating activity. Abstract: Human milk oligosaccharides (HMOs) have beneficial immune effects but the mechanisms of action are not well-understood. Here we study Toll-like receptor (TLR) signaling of the HMOs 2′-FL, 3-FL, 6′-SL, LNT2, and LNnT and their effect on cytokine production in human macrophages. 3-FL activated TLR2 and LNT2 activated all TLRs in a dose-dependent way. In an inhibition assay, 2′-FL, 6′-SL, and LNnT inhibited TLR5 and 7, while 3-FL inhibited TLR5, 7, and 8. 6′-SL showed a synergistic effect on ssRNA40-induced TLR8 activation. In addition, we measured HMO-induced cytokine production in THP1 macrophages. IL-10 and TNFα were induced by LNT2, and the effects were NF-κB dependent, while the other HMOs had minor effects. The potent effects of LNT2 might be explained by the unique N-acetylglucosamine end that binds to leucine-rich repeats on TLRs. Our data suggest that the effects of HMOs on TLR signaling and immunomodulation of macrophages are HMO-structure dependent.